2013
DOI: 10.1007/s00401-013-1208-4
|View full text |Cite|
|
Sign up to set email alerts
|

The role of pro-inflammatory S100A9 in Alzheimer’s disease amyloid-neuroinflammatory cascade

Abstract: Pro-inflammatory S100A9 protein is increasingly recognized as an important contributor to inflammation-related neurodegeneration. Here, we provide insights into S100A9 specific mechanisms of action in Alzheimer’s disease (AD). Due to its inherent amyloidogenicity S100A9 contributes to amyloid plaque formation together with Aβ. In traumatic brain injury (TBI) S100A9 itself rapidly forms amyloid plaques, which were reactive with oligomer-specific antibodies, but not with Aβ and amyloid fibrillar antibodies. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
191
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(202 citation statements)
references
References 48 publications
(72 reference statements)
10
191
1
Order By: Relevance
“…The main receptors for S100A8, S100A9 and calprotectin are TLR4, which represent the dominant receptor for the S100A8/S100A9 signalling pathway, as well as RAGE; however, the specific receptors and pathways for S100A8, S100A9 and calprotectin are mainly dependent on the cell type . For example, activated microglia produces significantly greater levels of S100A9 in Alzheimer's disease . A previous study indicated that both TLR4 and RAGE proteins were overexpressed in pancreatitis, as well as highlighting the ability of S100A9 to activate the IL‐17 signalling pathway and regulate the expression of inflammatory factors by binding to the cell surface receptors TLR4 and RAGE proteins .…”
Section: Discussionmentioning
confidence: 97%
“…The main receptors for S100A8, S100A9 and calprotectin are TLR4, which represent the dominant receptor for the S100A8/S100A9 signalling pathway, as well as RAGE; however, the specific receptors and pathways for S100A8, S100A9 and calprotectin are mainly dependent on the cell type . For example, activated microglia produces significantly greater levels of S100A9 in Alzheimer's disease . A previous study indicated that both TLR4 and RAGE proteins were overexpressed in pancreatitis, as well as highlighting the ability of S100A9 to activate the IL‐17 signalling pathway and regulate the expression of inflammatory factors by binding to the cell surface receptors TLR4 and RAGE proteins .…”
Section: Discussionmentioning
confidence: 97%
“…S100A8/9 proteins are also reported to increase during age-related inflammatory diseases including obesity (Nagareddy et al, 2014), cardiovascular disease (Ma et al, 2012), Alzheimer’s disease (Wang et al, 2014), and in the aged prostate (Yanamandra et al, 2009). This implies these proteins may provide an endogenous, local signal 1 for NLRP3 inflammasome activation and may be universal biomarkers of inflammation (Vogl et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While S100A9 is not a very abundant blood protein, it is an amyloidogenic protein in itself that is strongly expressed during inflammation including inflammation‐associated AD . In vitro S100A9 and Aβ interact and seem to act as synergistic partners in amyloid formation . Like with fibrinogen, any role of S100A9 in the AD process is unclear, but the focus is again turned towards inflammatory brain processes affecting the AD progression.…”
Section: Blood Proteinsmentioning
confidence: 99%
“…Like with fibrinogen, any role of S100A9 in the AD process is unclear, but the focus is again turned towards inflammatory brain processes affecting the AD progression. Interestingly, traumatic brain injury promotes S100A9 amyloid formation, and these plaques may possibly serve as precursor plaques for Aβ …”
Section: Blood Proteinsmentioning
confidence: 99%